Pengaruh Dampak Perilaku Konsumen Terhadap Stabilitas Moneter di Era Digital - Juleha Safitri; Yetti Afrida Indra (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to explore the impact of consumer behavior on monetary stability in the digital era. This type of associative quantitative research approach. Ddata was collected from 52 respondents through questionnaires who are active consumers through online surveys. Data analysis techniques in using multiple regression analysis methods for data analysis. The results of the analysis show that consumer behavior, including online shopping patterns, the use of financial applications, and trust in digital payment systems, which have a significant effect on monetary stability are online shopping patterns, and trust in digital payment systems. Meanwhile, the use of financial applications has no effect. The findings indicate a close relationship between consumption decisions and responses to monetary policy. The results of this study provide insight for policymakers in formulating strategies to maintain monetary stability during rapid development of digital technology